Rosenzweig and Heidegger : between Judaism and German philosophy - Gordon, Peter Eli. (Berkeley, LA : University of California Press, 2003)
Franz Rosenzweig (1886-1929) is widely regarded today as one of the most original and intellectually challenging figures within the so-called renaissance of German-Jewish thought in the Weimar period. The architect of a unique kind of existential theology, and an important influence upon such philosophers as Walter Benjamin, Martin Buber, Leo Strauss, and Emmanuel Levinas, Rosenzweig is remembered chiefly as a "Jewish thinker," often to the neglect of his broader philosophical concerns
Introduction: Germans, Jews, and the Transformation of Weimar Philosophy -- Toward Metaphysics: Cohen's Opus Postumum and the Origins of the New Thinking -- Hegel's Fate: The Emergence of Finitude in Rosenzweig's Hegel and the State -- Beyond Metaphysics: Rosenzweig's Star (Part I) -- Redemption-in-the-World: Rosenzweig's Star (Part II) -- "Facing the Wooded Ridge": The Hebrew Bible in the German Horizon -- "An Irony in the History of Spirit": Rosenzweig, Heidegger, and the Davos Disputation.
Includes index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Rosenzweig, Franz, -- 1886-1929 -- Criticism and interpretation; Heidegger, Martin, -- 1889-1976 -- Criticism and interpretation; Heidegger, Martin, -- 1889-1976; Rosenzweig, Franz, -- 1886-1929; Judaism and philosophy; Judaism -- Germany -- 20th century; Jewish philosophy -- Germany -- 20th century; Jews -- Germany -- 1918-1933.; Judaïsme et philosophie; Philosophie juive -- Allemagne -- 20e siècle.; PHILOSOPHY -- Eastern; PHILOSOPHY -- Political; Jewish philosophy; Jews; Judaism; Judaism and philosophy; Germany; Filosofie; Jodendom; Duitsland; 1900 - 1999; Criticism, interpretation, etc